A MEMS based valveless micropump for biomedical applications - Van der Merwe, Schalk Willem (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScEng (Mechanical and Mechatronic Engineering))--University of Stellenbosch, 2010.